An easy, rapid and inexpensive method to monitor tributyltin (TBT) toxicity in the laboratory - Cruz, Andreia
Tributyltin (TBT) contamination remains a major problem worldwide. Many laboratories are committed to the development of remediation methodologies that could help reduce the negative impact of this compound in the environment. Furthermore, it is important to have at hand simple methodologies for evaluating TBT toxicity in the laboratory, besides the use of complex and costly analytical instrumentation. With that purpose, a method was adapted that is based on the inhibition of growth of an indicator strain, Micrococcus luteus ATCC 9341, under TBT. Different types of matrices, of TBT concentrations and sample treatments were tested. The results herein reported show that the bioassay method can be applied for both aqueous and soil samples and also for a high range of TBT concentrations (at least up to 500 μmol/L). Besides being cheap and easy to perform, it can be performed in any laboratory. Additionally, one possible application of the method to monitor TBT degradation is presented as an example.